PRAKTIK YOGA ASANA DALAM MENINGKATKAN KEBUGARAN DAN KECERDASAN SISWA DI SD NEGERI 19 DAUH PURI - Anggun Wendraswari; Ni Nyoman Perni; I Gusti Made Widya Sena (Pangkaja: Jurnal Agama Hindu, 2023)
The development of science and technology provides convenience in life but not every convenience has a positive impact in the world of education. Precisely with these various conveniences further away from the meaning and meaning of life. Therefore, SD Negeri 19 Dauh Puri provides a learning method that can improve the fitness and intelligence of students at SD Negeri 19 Dauh Puri, namely practicing yoga asanas. The problems in this research are: (1). The stages of practicing yoga asanas in improving the fitness and intelligence of students at SD Negeri 19 Dauh Puri. (2). How yoga asanas work in improving the fitness and intelligence of students at SD Negeri 19 Dauh Puri. (3). Perceptions of yoga asanas, both perceptions from schools, parents and students. The theory used in this study is practical theory to reveal the stages of yoga asanas in improving the fitness and intelligence of students at SD Negeri 19 Dauh Puri. Behaviorism theory is used to examine how yoga asanas work in improving the fitness and intelligence of students at SD Negeri 19 Dauh Puri and perceptions of yoga asanas, which include perceptions from schools, parents, and students. The factors that encourage students to learn yoga asanas at SD Negeri 19 Dauh Puri, namely: health, fitness and intelligence factors, both spiritual, emotional and intellectual. The yoga asana learning system at SD Negeri 19 Dauh puri includes: the preparation stage, the preliminary stage, the core stage, the relaxation stage, and the closing stage. The analysis includes: The practice of yoga asanas that the solar namaskara movement and other asanas have a strong influence on the health of the body related to the respiratory system, blood circulation, digestion, nerves, skin, muscles, bones, urinary system, glands and others. On the other hand, the perception of schools, parents and students towards yoga asanas is good. This is indicated by the benefits of practicing yoga asanas that are practiced at SD Negeri 19 Dauh Puri, providing many benefits to students, especially in the fitness and intelligence of elementary school students.